2021
DOI: 10.3390/ijerph18105243
|View full text |Cite
|
Sign up to set email alerts
|

Scutellaria baicalensis and Their Natural Flavone Compounds as Potential Medicinal Drugs for the Treatment of Nicotine-Induced Non-Small-Cell Lung Cancer and Asthma

Abstract: Flavonoids as the largest group of natural phytochemical compounds have received significant attention, as demonstrated by clinical trials, due to their chemotherapeutic and/or pharmacological effects against non-small-cell lung cancer (NSCLC) and asthma. Scutellaria baicalensis (S. baicalensis), known as one of the most popular medicinal plants and used in several countries, contains natural active flavone constituents, with the major compounds of the roots being baicalein, baicalin, wogonin, wogonoside and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 106 publications
0
25
0
Order By: Relevance
“…However, combination therapy of monoclonal antibody-based immunotherapy and chemotherapeutic agents has been shown to be a promising treatment strategy for NSCLC [ 15 ]. In addition, natural flavonoids present in fruits (e.g., citrus) in combination with chemotherapeutic agents, such as cisplatin, have shown anti-NSCLC effects, demonstrated by inhibition of the α7nAChR-mediated signaling pathways involved in cellular processes including proliferation, inflammation and anti-apoptosis [ 13 , 16 ].The health benefits of fruits are due to the high levels of bioactive flavonoids they contain, such as PCs and ACNs [ 17 , 18 ]. A large number of studies have documented the health benefits of natural flavonoids derived from fruits and plant foods, in relation to their biological attributes such as anti-diabetes/anti-cancer activity, reducing cardiovascular diseases and improving the blood lipid profile [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, combination therapy of monoclonal antibody-based immunotherapy and chemotherapeutic agents has been shown to be a promising treatment strategy for NSCLC [ 15 ]. In addition, natural flavonoids present in fruits (e.g., citrus) in combination with chemotherapeutic agents, such as cisplatin, have shown anti-NSCLC effects, demonstrated by inhibition of the α7nAChR-mediated signaling pathways involved in cellular processes including proliferation, inflammation and anti-apoptosis [ 13 , 16 ].The health benefits of fruits are due to the high levels of bioactive flavonoids they contain, such as PCs and ACNs [ 17 , 18 ]. A large number of studies have documented the health benefits of natural flavonoids derived from fruits and plant foods, in relation to their biological attributes such as anti-diabetes/anti-cancer activity, reducing cardiovascular diseases and improving the blood lipid profile [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review showed that flavone-rich extracts from Scutellaria baicalensis , and baicalein, baicalin, wogonin, wogonoside and oroxylin A, in particular, serve as potential adjuvant agents for the treatment of nicotine-induced NSCLC. These compounds exert anti-inflammatory, anti-angiogenesis, anti-proliferative and apoptotic/autophagic effects through inhibiting several cellular signaling pathways as potential molecular mechanisms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Several studies verify that baicalein has a broad anti-tumour activity against breast cancer cells, hepatocellular carcinoma, leukaemia, colon, lung and prostate cancer cells. [7] Furthermore, baicalein has beneficial effects in the treatment of gliomas, but high therapeutic doses are needed. [8] Since baicalein is known to be rapidly metabolised in vivo, [9] an improvement of metabolic stability is necessary to enhance the therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%